Dual strategies for peptidoglycan discrimination by peptidoglycan recognition proteins (PGRPs) - Swaminathan, Chittoor P. (National Academy of Sciences, 2006)
The innate immune system constitutes the first line of defense against microorganisms in both vertebrates and invertebrates. Although much progress has been made toward identifying key receptors and understanding their role in host defense, far less is known about how these receptors recognize microbial ligands. Such studies have been severely hampered by the need to purify ligands from microbial sources and a reliance on biological assays, rather than direct binding, to monitor recognition. We used synthetic peptidoglycan (PGN) derivatives, combined with microcalorimetry, to define the binding specificities of human and insect peptidogycan recognition proteins (PGRPs). We demonstrate that these innate immune receptors use dual strategies to distinguish between PGNs from different bacteria: one based on the composition of the PGN peptide stem and another that senses the peptide bridge crosslinking the stems. To pinpoint the site of PGRPs that mediates discrimination, we engineered structure-based variants having altered PGN-binding properties. The plasticity of the PGRP-binding site revealed by these mutants suggests an intrinsic capacity of the innate immune system to rapidly evolve specificities to meet new microbial challenges.